A flexible selection tool for the inclusion of soil biology methods in the assessment of soil multifunctionality. (March 2022) - Zwetsloot, Marie J.; Bongiorno, Giulia; Barel, Janna M.; di Lonardo, D. Paolo; Creamer, Rachel E.
Abstract: Soil biota contribute to the delivery of multiple soil functions. However, soil biological methods are highly underrepresented in the assessment of soil functionality in agricultural production systems. Here we present a flexible tool to support decision-making during the selection process of soil biological methods for monitoring soil functions. This tool is based on a structured and conceptual framework that connects soil biota to soil functions through their contribution to different soil processes. The methods assessed by the tool were selected as a result of a thorough literature review. Soil biology experts supported the development of the tool (i) by providing feedback on the reviewed methods through a survey and (ii) by determining the relevance of different soil biota to the soil processes related to soil multifunctionality during a workshop. The tool is freely accessible online at the Biological Soil Information System (BIOSIS) platform, where researchers or users with an understanding of research practices can interact with the tool to define the context of their assessment and preferences for technical criteria of the methods. By incorporating user input, this flexible tool can help inform a wide variety of research and assessment programs interested in applying soil biological methods to monitor soil multifunctionality at different scales. Graphical abstract: Image 1 Highlights: We developed a tool for selecting biological methods to assess soil functions. The tool is freely accessible online at the BIOSIS platform. The BIOSIS tool is flexible to consider context-specific requirements of users. The transparent setup of the tool allows for further development and collaboration.